2016
DOI: 10.1021/acs.jafc.6b02963
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Stearoyl-Acyl Carrier Protein Desaturase Genes from Olive (Olea europaea) in Relation to the Oleic Acid Content of the Virgin Olive Oil

Abstract: The specific contribution of different stearoyl-ACP desaturase (SAD) genes to the oleic acid content in olive (Olea europaea) fruit has been studied. Towards that end, we isolated three distinct cDNA clones encoding three SAD isoforms from olive (cv. Picual), as revealed by sequence analysis. The expression levels of olive SAD genes were determined in different tissues from Picual and Arbequina cultivars, including developing mesocarp and seed, together with the unsaturated fatty acid content. Lipid and gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…In a previous study, the oil content of different olive varieties was significantly differentiated in the fast oil accumulation stage ( Figure S6). Several LPGs have different expression patterns between the two varieties; this result is similar to that of a study on the gene expression levels of OeFAD2 [64], OeFAD3 [65], and OeSACPD [66] during fruit development between two olive varieties ('Picual' and 'Arbequina'). The expression levels of some LPGs, such as OeACC1, OeDGAT1, OeKASII.6, and OeLPAAT2, were consistent with the oil accumulation trend.…”
Section: The Expression Pattern Of Oebzip Was Related To Fruit Develosupporting
confidence: 83%
“…In a previous study, the oil content of different olive varieties was significantly differentiated in the fast oil accumulation stage ( Figure S6). Several LPGs have different expression patterns between the two varieties; this result is similar to that of a study on the gene expression levels of OeFAD2 [64], OeFAD3 [65], and OeSACPD [66] during fruit development between two olive varieties ('Picual' and 'Arbequina'). The expression levels of some LPGs, such as OeACC1, OeDGAT1, OeKASII.6, and OeLPAAT2, were consistent with the oil accumulation trend.…”
Section: The Expression Pattern Of Oebzip Was Related To Fruit Develosupporting
confidence: 83%
“…However, in the experiment with nitrogen, increasing sad expression did not directly correlate with the measured amounts of C18:1n9 for the different treatments. It is known that there are many sad genes in plants (Kachroo et al, 2007;Parvini et al, 2016), which may also exist in green algae but these…”
Section: Transcript Expression Of Fatty Acid Biosynthesis Genesmentioning
confidence: 99%
“…These results are in agreement with recent studies indicating the usage of phospholipids as substrate of NADH, NADH-cytochrome b5 reductase and cytochrome b5 as the electron donor by FAD2 and FAD3 enzymes, respectively. Moreover, FAD6 and FAD7/8 members utilise glycolipids as acyl carriers whereas, NAD(P)H, ferredoxin-NAD(P) reductase and ferredoxin are used as an electron donor system [51,52]. Catalytic activity is the prime molecular function among FAD proteins, which might reflect their mode of action.…”
Section: Analyses Of Predicted Biological Role Molecular Function Anmentioning
confidence: 99%
“…Previous studies on the expression patterns of FAB2 genes in oil crops revealed that some FAB2 genes were mainly upregulated in embryo and seed tissues. For example, the OeSAD2 gene in olive appeared to be the main gene contributing to the oleic acid content of the olive fruit as per lipid and gene expression levels [57]. In maize, the expression level of the ZmSAD1 gene was the highest in the embryo, followed by that in the endosperm, leaf, seed, shoot, tassel, ear, ovule, anther and shoot apical meristem tissues [58].…”
Section: Drought Stress Effects On the Expression Profiles Of Sunflowmentioning
confidence: 99%